2003
DOI: 10.1111/j.1545-5300.2003.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Burden in Schizophrenia Caregivers: Impact of Family Psychoeducation and Awareness of Patient Suicidality

Abstract: Family caregivers of persons with schizophrenia and other psychotic disorders experience high levels of burden. Although a number of patient and caregiver predictors of burden have been identified, little research has investigated the contributions of patient depression, suicidal ideation, and substance abuse. In addition, family psychoeducation interventions have reduced patient symptoms, as well as inpatient treatment utilization; however, it is not known whether or not these interventions reduce family burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 41 publications
5
101
1
4
Order By: Relevance
“…Caregiving burden also includes environmental burden and is associated with stigmatization and social isolation by neighbors or other acquaintances [7]. McDonnell et al [8] reported that caregiver's awareness of patient's suicidal ideation and long-term cost implications for care contribute to the burden and were significant predictors of the burden of care. Other studies show that caregivers are at increased risk of deterioration in health and functioning [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Caregiving burden also includes environmental burden and is associated with stigmatization and social isolation by neighbors or other acquaintances [7]. McDonnell et al [8] reported that caregiver's awareness of patient's suicidal ideation and long-term cost implications for care contribute to the burden and were significant predictors of the burden of care. Other studies show that caregivers are at increased risk of deterioration in health and functioning [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…It is a self-administered instrument with 22 items, which explores negative effects on the caregiver in relation to physical and mental health, social activities, and economic resources. Each question is evaluated on a Likert scale with five possible responses from ''never'' (1) to ''almost always'' (5). Total scores range from 22-110.…”
Section: Methodsmentioning
confidence: 99%
“…Demands of caregiving include paying for psychiatric treatment, supervision of the patient, dealing with societal stigma associated with mental illness, and emotional distress that may result from symptoms of family member's disorder [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, however, have suggested that it is unlikely that caregivers, particularly those of patients with a long history of illness, will change their views of patients after a short PEP intervention. Further, the difficulty in engaging patients and their carers during PEP has made the outcomes of the programs inconclusive [21][22][23] . In the United States, family psychoeducation interventions are currently considered one of five evidence-based psychosocial interventions for persons with severe mental illness, particularly those with schizophrenia 24 .…”
mentioning
confidence: 99%